#### Answer

f(-2)=-$\frac{9}{2}$

#### Work Step by Step

f(x)=$\frac{x^{2}+5}{x}$
f(-2)=$\frac{(-2)^{2}+5}{-2}$=
=$\frac{4+5}{-2}$=-$\frac{9}{2}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

f(-2)=-$\frac{9}{2}$

f(x)=$\frac{x^{2}+5}{x}$
f(-2)=$\frac{(-2)^{2}+5}{-2}$=
=$\frac{4+5}{-2}$=-$\frac{9}{2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.